Effect of Dietary Supplementation of Lauric Acid on Performance and Carcass Characteristics in Commercial Broiler Chicken - Bhalsing, Jivan; D. Nagalakshmi; M. Venkateshwarlu; S.V. Rama Rao (Indian Journal of Animal Nutrition, 2026)
An experiment was conducted to evaluate the effect of dietary lauric acid supplementation as alternative to antibiotic growth promoter (AGP) at graded levels on performance and carcass traits in commercial broilers. Three-hundred-day-old commercial broiler chicks were randomly allotted to 6 dietary treatments with 10 replicates of 5 chicks in each. Corn soyabean meal based basal diet (BD) was formulated for pre-starter (1-2 weeks), starter (3-4 weeks) and finisher (5-6 weeks) phases without antibiotic growth promoter (negative control). Positive control diet was the BD having 0.035% chlortetracycline as AGP. Remaining four experimental diets were formulated by supplementing lauric acid to BD at rate of 0.05% (LA-50), 0.075% (LA-75), 0.1% (LA-100) and 0.2% (LA-200), respectively. Body weights, feed intake and feed conversion ratio (FCR) were measured at weekly intervals. At the end of 6th week, one bird from each replicate was selected randomly for studying carcass characteristics. Overall body weight gain (BWG) was higher (P<0.05) in chicks fed LA supplemented diets compared to BD fed chicks. Highest BWG was obtained in chicks fed LA-50 diet than those fed on either AGP or BD and was comparable to those fed LA-75 diet. Higher feed intake was recorded in birds fed diets supplemented with LA-75 diets followed by LA-50, AGP, LA-200 and LA-100 fed birds. The FCR during all the phases was significantly (P<0.05) improved in LA-50 compared to other dietary groups. The dressing percentage was higher (P<0.05) with LA-50 compared to AGP fed birds, while at higher levels of LA supplementation, the dressing percentage was either comparable or higher than AGP or BD fed birds. No difference with regard to breast, liver and gizzard weights was observed with LA supplementation. Based on the results it could be concluded that, lauric acid can be a replacer of antibiotic growth promoter and lower dose of lauric acid (0.05%) used in the present study was sufficient in improving performance and dressing percentage in broilers.